Massive Hemothorax due to a Rare Entity: Dilemma of ICD Insertion!! A Case Report - Prabhav Chhaperwal; Masti Nagendra Rao Vijai; Gurbinder Singh Suri; Uma Shankar Garg; Kiran Kumar Parate; Suraj Kapoor (Annals of Cardiac Anaesthesia)
Intercostal artery aneurysms are a type of vascular abnormality that poses a potential risk of rupture, which could lead to life-threatening hemothorax. This case report presents a young male who experienced a rupture of an intercostal artery aneurysm and subsequently suffered from a massive hemothorax after engaging in strenuous physical activity. The current case study sheds light on the difficulties and lessons learned in managing such cases in peripheral settings, including the dilemma of whether to insert an intercostal chest drain (ICD). The patient was ultimately diagnosed with a rare clinical entity known as rupture of right posterior intercostal artery aneurysm with massive hemothorax.